Outsourcing Decisions in the Bicycle Manufacturing Industry: Raleigh and Schwinn Bicycles. - Pan, Yufu (2009)
Outsourcing has already become a common trend in the modern business environment and a strategic tool employed by lots of companies in the world. However, outsourcing does not always bring benefits to companies which resort to it. The key point here in this case lies in that the decisions made by top managers in companies related to outsourcing could have a huge impact on themselves. So in order to examine the significant influences that outsourcing could bring to companies and investigate the importance of decisions made related to outsourcing, two particular companies which are Raleigh Bicycles and Schwinn Bicycles have been chosen to be evaluated and analyzed in this dissertation. The case study research method has been used as the main methodology throughout this entire dissertation. After the evaluation and analysis of the two companies, the predefined questions have been resolved and some conclusions and recommendations have been developed as well.